Learning orientation as moderating factor in stimulating knowledge sharing - Suzilawati Ibrahim, 1978-, author; Low, Hock Heng, 1963-, supervisor; Fakulti Pengurusan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D (Pengurusan)) - Universiti Teknologi Malaysia, 2016